2007
DOI: 10.1111/j.1600-0668.2006.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of permeable and hygroscopic lightweight structures on thermal comfort and perceived IAQ in a cold climate

Abstract: Limited knowledge is available about building envelope and ventilation system interactions with consequent effects on indoor climate. To take such effects adequately into account in design and construction of buildings, solid scientific data explaining the significance of the phenomena studied are needed. We have demonstrated that moisture exchange has evidently enough importance to be taken into account in future building simulation tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…While its thermal analogue is generally accepted and widely used, the validity of Eqs. (11)(12) still requires verification. Therefore interior moisture buffering simulations are performed with different surface area's (40 m² and 100 m²) of single finishes, and with combinations of different finishes (total surface area: 60 m²).…”
Section: Room-enclosure Mbp Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…While its thermal analogue is generally accepted and widely used, the validity of Eqs. (11)(12) still requires verification. Therefore interior moisture buffering simulations are performed with different surface area's (40 m² and 100 m²) of single finishes, and with combinations of different finishes (total surface area: 60 m²).…”
Section: Room-enclosure Mbp Characterisationmentioning
confidence: 99%
“…Several authors stress the importance of such interior moisture buffering in the global interior humidity evolution, supported by measurements [9][10][11][12] and simulations [12][13][14][15][16]. Interior moisture buffering is indeed shown to positively affect energy consumption, component durability, thermal comfort and air quality [10,12,15,17,18]. The development of sustainable, durable, healthy and comfortable buildings hence requires the quantitative and/or qualitative assessment of interior moisture buffering.…”
Section: Introductionmentioning
confidence: 99%
“…Research into humidity buffering materials has been motivated by a number of factors: the thermal comfort of building occupants is closely related to the humidity of the indoor air (Fang et al, 1998a(Fang et al, , 1998bKurnitski et al, 2007;Simonson et al, 2002); certain environments require tight humidity control to prevent damage to their contents (e.g. historic buildings, museums and art galleries) (Padfield, 1998); excessive humidity can promote dust mite populations and the growth of unsightly mould, both of which are known to be allergens with potentially serious health effects (Howieson, 2003;Oreszczyn et al 2006); condensation and damp can significantly reduce the life of building materials; and finally, passive control of humidity by the fabric of the building may reduce or even remove the need for mechanical air conditioning, reducing the amount of energy required (Osanyintola and Simonson, 2006) as well as the running cost of the building.…”
Section: Introductionmentioning
confidence: 99%
“…Although, interior finishes (wooden floors, gypsum plasters,…) and interior objects (books, carpets, furniture,…) absorb or release moisture when exposed to a variation in relative humidity, and accordingly may yield a passive control of interior humidity. Measurements (Padfield, 1998;Simonson, 2004a;Kurnitski, 2007) and simulations (Kurnitski, 2007;Rode, 2004;Holm, 2004;Simonson, 2004b) have shown that such moisture ex-…”
Section: Introductionmentioning
confidence: 99%